Clinical Profile of Proptosis in Dr. M. Djamil General Hospital Padang - Feby Helwina; Ardizal Rahman (HM Publisher, 2022)
Background. Proptosis is a condition that describes a protrusion or forward shift of the eyeball and is commonly used to describe the condition of protrusion of the eyeball. Proptosis generally occurs due to a mismatch between the orbital capacity and the volume of the tissue structure in the orbital cavity. It is a common manifestation of a wide variety of diseases of the structures in and around the orbit and in some systemic diseases. This study aimed to describe the clinical profile of proptosis patients in Dr. M. Djamil General Hospital Padang. Methods. We reviewed the medical record of the oncology subdivision of ophthalmology patients associated with proptosis retrospectively, such as inflammatory, infectious, tumors, and vascular, admitted to the M.Djamil General Hospital in Padang from January 2019 to August 2020. The ocular and systemic history and examination details were recorded. Results. We found 48 proptosis patients from January 2019 to August 2020, consisting of 30(62.5%) males and 18(37,5%) females. The majority of subjects were in the Adult age group (79,17%). Unilateral and bilateral proptosis were found in 37(77%) and 11(23%), with mostly axial proptosis (83,33%). Inflammatory tumors were found in 17(35,41) and 29(60%) patients. Conclusion. Proptosis is a common clinical feature of various local and systemic diseases. Even though proptosis have diverse etiology and pathogenesis, they usually present with similar clinical manifestation. Proptosis may be one of the most important keys to disease guidance from a close structure that requires a multidisciplinary approach.